2020
DOI: 10.20524/aog.2020.0518
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of eosinophils in the gastrointestinal tract of children with no organic disease

Abstract: Background This study aimed to assess the eosinophil (eos) density of the mucosa of the gastrointestinal (GI) tract in children undergoing endoscopic procedures following an extensive workup, without diagnosis of an organic disease. Methods Biopsies from GI endoscopies performed at 3 major children’s hospitals (Athens, Madrid and Rome), between January 2012 and June 2018, were evaluated by a single pathologist in each center. Peak eos counts were expressed /high power f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…Mucosal eosinophil numbers are thought to increase progressively from the proximal small intestine to the cecum as reported by pediatric studies ( Lowichik and Weinberg, 1996 ; DeBrosse et al, 2006 ; Kiss et al, 2018 ; Koutri et al, 2020 ), although an opposite gradient is found in mice ( Mowat and Agace, 2014 ; Brown and Esterházy, 2021 ). Eosinophils represent around 20% of the leukocyte population in the lamina propria of the proximal small intestine ( Jung and Rothenberg, 2014 ).…”
Section: Intestinal Mucosal Eosinophils In Homeostasis and Inflammationmentioning
confidence: 75%
“…Mucosal eosinophil numbers are thought to increase progressively from the proximal small intestine to the cecum as reported by pediatric studies ( Lowichik and Weinberg, 1996 ; DeBrosse et al, 2006 ; Kiss et al, 2018 ; Koutri et al, 2020 ), although an opposite gradient is found in mice ( Mowat and Agace, 2014 ; Brown and Esterházy, 2021 ). Eosinophils represent around 20% of the leukocyte population in the lamina propria of the proximal small intestine ( Jung and Rothenberg, 2014 ).…”
Section: Intestinal Mucosal Eosinophils In Homeostasis and Inflammationmentioning
confidence: 75%
“…Some authors have proposed a rigorous definition of eosinophils that can be counted, which includes only cells filled with eosinophilic granules and in which both lobes of the nucleus are visible. 17 Applying this restrictive definition results in an underestimation of tissue eosinophilia. Histologic sections 5-µm thick often cut eosinophils perpendicularly to their bilobate nucleus, thus preventing the visualization of both lobes even though such cells are unequivocally eosinophils.…”
Section: Defining a Countable Eosinophil-what To Countmentioning
confidence: 99%
“…In a large multicentric paediatric cohort of biopsies 4 , the median peak eosinophil count/mm 2 and their interquartile ranges (in brackets) were: oesophagus 0 (0-0), stomach 10.2 (3.3-15.3), duodenum 56.1 (26.1-86.7), ileum 61.2 (49.0-91.8), cecum 76.5 (40.9-99.7), ascending colon 73.9 (49.5-131.4), transverse colon 66.3 (40.8-91.5), descending colon 66.3 (30.6-81.6), sigmoid colon 39.2 (27.8-51.0), rectum 25.5 (9.8-45.8), respectively. Saad 13 underlined that eosinophils were mainly observed within the lamina propria, and only rarely in the surface and crypt epithelium, such as in the cecum and the rectosigmoid tract, where they may be organised in small clusters.…”
Section: Normal Distribution Of Eosinophils In the Gastrointestinal T...mentioning
confidence: 99%
“…Different studies have tried to assess a range of normal eosinophil distribution in the GI tract in adults 3 while very few studies investigate distribution in the paediatric population 4 , 5 , consequently complicating the pathologist’s ability in identifying an abnormal number of eosinophils. Consensus recommendations for the diagnosis of EoGIDs are limited only to EoE, with some differences depending on the patients’ age 6 .…”
Section: Introductionmentioning
confidence: 99%